Learning to be capitalists entrepreneurs in Vietnam's transition economy - Kim, Annette Miae. (New York ; Oxford : Oxford University Press, 2008)
Examines Ho Chi Minh City's first generation of entrepreneurs to find that a city-wide reconstruction of cognitive paradigms enabled them and others to transform Vietnam from a poor centrally planned economy into one of the fastest-growing market economies in the world, despite ignoring conventional reform strategies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Capitalism -- Vietnam; Entrepreneurship -- Vietnam; Vietnam -- Economic policy